Economic Engineering of the Profit-Sharing System as an Effort to Improve the Welfare of Rice Farmers in Pinrang Regency - Abdul Halim (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Rice farming in Pinrang faces an imbalance in the distribution of profits between tenant farmers and landowners, which results in low incomes and increased economic vulnerability of farmers, especially when production is not optimal. This study aims to design and analyze a profit-sharing system for rice farming based on an economic engineering approach in Pinrang District, South Sulawesi. The current profit-sharing system shows inequality between tenant farmers and landowners, both in terms of profit sharing and production costs. The research method used a qualitative approach with the support of quantitative analysis through simulation of net income in two production scenarios (optimal and non-optimal). The results show that sharecroppers bear most of the farming costs, while profit sharing does not consider cost contributions fairly. Under non-optimal production conditions, tenant farmers' net income is below the minimum wage and close to the poverty line. The proposed farming economic engineering model is a 50:50 cost and yield sharing system and initial financing by the owner or financial institutions without interest. This system is considered more efficient and fair in increasing farmers' income and economic resilience. The findings can serve as a basis for regional policy formulation related to an equitable and sustainable profit-sharing system.